Management of patients with chronic hepatitis C failing repeated courses of interferon‐free direct acting antiviral combination therapy. Issue 2 (8th April 2019) - Kozbial, Karin; Al‐Zoairy, Ramona; Gschwantler, Michael; Stauber, Rudolf; Hametner, Stephanie; Laferl, Hermann; Strasser, Michael; Hayat‐Khayyati, Avida; Datz, Christian; Kramer, Ludwig; Schaefer, Benedikt; Maieron, Andreas; et al.
Summary: Background: Only few chronic hepatitis C patients treated with interferon (IFN)‐free direct acting antiviral (DAA) combinations fail to clear the virus. Most patients can be cured by retreatment with another DAA combination; however, some still fail to eradicate the virus. So far, little is known about how to best retreat these patients. In this study we summarise our real world experience of re‐retreatments. Methods: One hundred and two patients who completed a DAA‐retreatment after virological failure to an IFN‐free DAA therapy and reached at least follow‐up 12 were included in this study.Twenty‐one (20.6%) of them relapsed again after retreatment (mean age 50.0 ± 10.6, 18 male, three female, GT1a:8, GT1b:4, GT1c:1, GT3a:7; GT4:1; cirrhosis:15; resistance associated substitutions [RAS]: 17/19; relapse after:SOF/SMV:2; 3D ± RBV:4; SOF/DCV ± RBV:4; SOF/LDV ± RBV:6; SOF/VEL:3; SOF/VEL/VOX:1; EBV/GZV:1).Treatment duration and addition of RBV were at the discretion of the treating physician. These 21 patients were studied in detail. Results: Seventeen of the 21 patients finished a third DAA therapy: 13 achieved SVR12, three relapsed again (cirrhosis:2; SOF/VEL/RBV:GT3a; SOF/LDV/RBV:GT1a; EBV/GZV/SOF/RBV:GT1b), one was lost to follow‐up. One (GT1a, cirrhosis) achieved SVR12 after the third retherapy with 24 weeks of 3D/SOF/RBV, and one (GT3a, cirrhosis) achieved SVR4 after 24 weeks of glecaprevir/pibrentasvir, but died shortly thereafter. Overall, 95 (93.1%) of 102 patients achieved SVR12 after one or more retreatments. Sex, cirrhosis, genotype, RAS or baseline viral load were not associated with retreatment failure. Conclusion: Most patients with failure to a DAA therapy achieved SVR after retreatment with a different regimen; however, 13.7% of patients required multiple retreatments. Abstract : Linked Content This article is linked to Kozbial et al and Pandey papers. To view these articles, visit https://doi.org/10.1002/ygh2.341 and https://doi.org/10.1002/ygh2.342 .